Liver abscess caused by Ascaris lumbricoides: case report - Análida Elizabeth PINILLA; Myriam Consuelo LÓPEZ; Orlando RICAURTE; Blanca CASTILLO; Martha Isabel MURCIA; Rubén Santiago NICHOLLS; Sofía DUQUE; Luis Carlos OROZCO (Revista do Instituto de Medicina Tropical de São Paulo, 2001)
A case is reported of a woman who lived in a rural area with a chronic illness that consisted of weight loss and abdominal pain in the epigastrium and upper right quadrant. The initial diagnosis was a mass in the liver, which was later, demonstrated, both by direct and histological examination, to be an abscess caused by Ascaris lumbricoides. Eggs of Ascaris lumbricoides and abundant Charcot-Leyden Crystals were found.